Conformational and topological correlations in non-frustated triblock copolymers with homopolymers. Issue 3 (24th November 2020) - Buchanan, Natalie; Browka, Krysia; Ketcham, Lianna; Le, Hillary; Padmanabhan, Poornima
Abstract : The phase behavior of non-frustrated ABC block copolymers polymers, modeling poly(isoprene- b -styrene- b -ethylene oxide) (ISO), is studied using dissipative particle dynamic (DPD) simulations. Abstract : The phase behavior of non-frustrated ABC block copolymers polymers, modeling poly(isoprene- b -styrene- b -ethylene oxide) (ISO), is studied using dissipative particle dynamic (DPD) simulations. The phase diagram showed a wide composition range for the alternating gyroid morphology, which can be transformed to a chiral metamaterial. A quantitative analysis of topology was developed, that correlates the location of a block relative to the interface with the block's end-to-end distance. This analysis showed that the A-blocks stretched as they were located deeper in the A-rich region. To further expand the stability of the alternating gyroid phase, A-selective homopolymers of different lengths were co-assembled with the ABC copolymer at several compositions. Topological analysis showed that homopolymers with lengths shorter than or equal to the A-block length filled the middle of the networks, decreasing packing frustration and stabilizing them, while longer homopolymers stretched across the network but allowed for the formation of stable, novel morphologies. Adding homopolymers to triblock copolymer melts increases tunability of the network, offering greater control over the final stable phase and bridging two separate regions in the phase diagram.